IDENTIFIKASI BAHAYA DAN PENILAIAN RISIKO DI KAWASAN WISATA LEUWI KENIT, CILETUH PALABUHANRATU UGG: HAZARD IDENTIFICATION AND RISK ASSESSMENT IN THE LEUWI KENIT TOURISM AREA, CILETUH PELABUHANRATU UGG - Surahman, Dikky; Pratiwi, Santi Dwi (Journal of Geoscience Engineering and Energy, 2024)
Ciletuh Palabuhanratu as the first geopark in West Java which has been recognized by UNESCO since 2018, is famous as the first land in western Java. One of the natural tourist object in the Geopark area with the beauty of ancient rock structures aged more than 60 million years ago is the Leuwi Kenit natural tourist destination in Pasirpanjang Village, which has a very large number of tourists, but in certain periods there are often visitor accidents. This research aims to identify hazards and risk assessment, as well as risk control from hazards, with research objects including parking areas, entrance gates, access routes, play facilities, and exit routes. The research method is a qualitative Hazard Identification and Risk Assessment and mapping of danger points, literature studies, field observations, interviews with the community, tour guides and tourist attraction guards. Based on the results of the study, there are fifteen danger points in the Leuwi Kenit tourist attraction, some of which can occur when the activity is running with a range of risk relative status, namely low to high. Risk relative high status is recorded to have dominated with seven danger points, risk relative moderate status with six danger points, and risk relative low with two danger points. According to the results of the study, there are fifteen danger points in the Leuwi Kenit tourist attraction, some of which can occur when the activity is running with a range of risk relative status, namely low to high. Risk relative high status is recorded as dominant with seven danger points, risk relative moderate status with six danger points, and risk relative low status with two danger points. The results of the risk assessment show that the risk status is included in potential hazards with high and medium hazard risk levels, management attention and control planning are needed. Alternative risk controls that can be implemented to minimize the occurrence of risk are administrative, engineering, and elimination approaches. Forms of risk avoidance applications such as making paths according to safe standards, making information boards for hazard location points, and rearranging amusement ride according to safety standards at Leuwi Kenit.